2001
DOI: 10.1038/sj.ejhg.5200633
|View full text |Cite
|
Sign up to set email alerts
|

A molecular genetic service for diagnosing individuals with familial hypercholesterolaemia (FH) in the United Kingdom

Abstract: A genetic diagnostic service for familial hypercholesterolaemia (FH) has been established over the last 4 years in the Clinical Molecular Genetics Laboratory at Great Ormond Street Hospital for Children NHS Trust (GOSH), London. In total there have been 368 referrals; 227 probands and 141 family members, which have come from a number of lipid clinics and from general practitioners. FH is caused by mutations in the lowdensity lipoprotein receptor gene (LDLR) and these are analysed by SSCP, DNA sequencing and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
1
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 34 publications
10
60
1
5
Order By: Relevance
“…The probands were reported to have an unusual phenotype of aggravated hypercholesterolaemia that was complicated with premature coronary arterial disease, although remaining responsive to The case we present in this paper is a double heterozygote for the p.Leu479Pro mutation in the LDLR gene and the common p.Arg3527Gln mutation in the APOB gene. The p.Leu479Pro mutation has been reported previously, 5,14,15 and we have found this mutation in 4/414 ( 1%) of our unrelated patients with detected mutations. Although no functional studies have been performed to confirm its pathogenicity, the p.Leu479Pro mutation occurs in the epidermal growth factor spacer domain of the LDLR protein that is required for acid-dependent dissociation of the receptor from its ligand during recycling, and the mutation may interfere with receptor recycling.…”
Section: Discussionmentioning
confidence: 79%
“…The probands were reported to have an unusual phenotype of aggravated hypercholesterolaemia that was complicated with premature coronary arterial disease, although remaining responsive to The case we present in this paper is a double heterozygote for the p.Leu479Pro mutation in the LDLR gene and the common p.Arg3527Gln mutation in the APOB gene. The p.Leu479Pro mutation has been reported previously, 5,14,15 and we have found this mutation in 4/414 ( 1%) of our unrelated patients with detected mutations. Although no functional studies have been performed to confirm its pathogenicity, the p.Leu479Pro mutation occurs in the epidermal growth factor spacer domain of the LDLR protein that is required for acid-dependent dissociation of the receptor from its ligand during recycling, and the mutation may interfere with receptor recycling.…”
Section: Discussionmentioning
confidence: 79%
“…An unequivocal diagnosis can also be made by the carriage of a pathogenic LDLR mutation, identified by a DNA-based test. 7 The utility of DNA testing remains limited however, as a mutation is currently identified in only 30-60% of clinically identified cases. 8 Despite these potential difficulties, a recent modelling exercise and review have suggested that cascade testing based on lipid or genetic testing in the relatives of known FH probands is cost effective in terms of life-years gained.…”
Section: Familial Hypercholesterolaemia (Fh) Cascade Screeningmentioning
confidence: 99%
“…It has proven feasible, even for FH, to design rapid screens that detect a significant fraction of FH mutations. 18 Most of the evidence suggests that common genetic variations will explain a significant fraction of the risk of common diseases, including CHD. 19 The value of genetic testing in cardiology will become clear only when it has been implemented on a large scale.…”
Section: Multilocus Testingmentioning
confidence: 99%